Controlling the Immune Suppressor: Transcription Factors and MicroRNAs Regulating CD73/NT5E - Kordaß, Theresa; Osen, Wolfram; Eichmüller, Stefan B. (Frontiers in Immunology, 2018)
The NT5E (CD73) molecule represents an ecto-5’-nucleotidase expressed on the cell surface of various cell types. Hydrolyzing extracellular AMP into adenosine and inorganic phosphate, NT5E performs numerous homeostatic functions in healthy organs and tissues. Importantly, NT5E can act as inhibitory immune checkpoint molecule, since free adenosine generated by NT5E inhibits cellular immune responses, thereby promoting immune escape of tumor cells. MicroRNAs (miRNAs) are small noncoding RNA molecules regulating gene expression on post-transcriptional level through binding to mRNAs, resulting in translational repression or degradation of the targeted mRNA molecule. In tumor cells, miRNA expression patterns are often altered which in turn might affect NT5E surface expression and eventually influence the efficacy of anti-tumor immune responses. This review describes the diverse roles of NT5E, summarizes current knowledge about transcription factors controlling NT5E expression, and highlights the significance of miRNAs involved in the post-transcriptional regulation of NT5E expression.